Integrated Non-Digital Media Innovation ‘Space Capsule’ to Train Spatial Visualization Skills in Solid Geometry for Students - Alia, Hilma; Lisnani, Lisnani; Widyawati, Hesti; Walker, Justin; Azhar, Riza Haikal (Department of Mathematics Education Program IPI Garut, 2026)
Tujuan penelitian ini menghasilkan media pembelajaran non-digital terintegrasi bernama